Nigeria Watch: Eight Report on Violence in Nigeria - (:unkn) unknown (My University, 2019)
There was a 1.4% increase in the number of violent deaths in Nigeria in 2018. Fatalities increased from 10,515 in 2017 to 10,665 in 2018.Main causes of violent deaths in Nigeria were crime, political issues, land issues, religious issues, cattle grazing and road accidents.Boko Haram conflict killed 2,135 in 2018, less than the 2,829 fatalities in 2017, accounting for 28% decrease.Cult related killings accounted for 453 deaths in 162 incidents while 238 people were killed in 76 kidnap incidents.In 2018, 2,331 victims were killed in 350 lethal incidents involving security operatives. Ogun maintained its position in 2018 as the state with the highest prevalence of fatal road accidents.The most dangerous states in Nigeria in 2018 included Borno, Zamfara, Benue, Kaduna and Adamawa. These states were mostly ravaged by the Boko Haram insurgency, banditry and pastoral conflicts. On the contrary, Ekiti, Gombe, Jigawa, Osun and Kebbi states were relativelypeaceful.
Keywords: African Research